Examining the Association of Personality Traits and Grit on Greek Students’ Wellbeing in Higher Education - Eirene Katsarou; Paraskevi Chatzipanagiotou (Education Sciences)
University student wellbeing, viewed as a crucial factor for academic achievement, has become a significant concern for educational systems worldwide due to the growing incidence of students with increased stress and emotional health problems. Adopting a cross-sectional research design, this study seeks to explore undergraduate students’ academic wellbeing within a Greek academic context by identifying profiles of academic wellbeing as reported by participants in our sample, examine the extent to which these profiles differ by their demographic characteristics, personality traits, and grit, and determine the effects of the big five personality traits and grit on student wellbeing. Data were collected using a convenience sampling method with 206 first-year Greek undergraduate students majoring in Agriculture and Forestry completing an online survey questionnaire. Cluster analysis revealed three distinct academic wellbeing profiles, i.e., low (‘the overwhelmed’), medium (‘the balanced’), and high (‘the resilient’), that statistically differed by gender, age, field of academic studies, grit level, and personality traits. No statistically significant association was found between overall student wellbeing, self-reported grit levels, and personality traits. However, stepwise multiple regression results showed that the grit subscale of consistency of interests negatively predicts certain aspects of student wellbeing outcomes leading to a decline in self-reported levels of wellbeing and increasing levels of negative emotions and meaninglessness. This study further discusses potential initiatives and interventions adopted to enhance student wellbeing in higher education.